SPREADING OF HEN GASTROINTESTINAL PARASITOSES - Kruchynenko, O. V. (Scientific Progress & Innovations, 2021)
In Ukraine, one of the most common hen gastrointestinal invasions are representatives of the protozoa of Eimeria spp. (Schneider, 1875) and nematodes Ascaridia galli (Schrank, 1788), Heterakis gallinarum (Schrank, 1788), Trichostrongulus tenuis (Mehlis, 1846), and helminths of Capillaria genus (Zeder, 1800). The causative agents of these parasitic diseases are localized in the gastrointestinal tract and are harmful to the host. These types of parasites impede the development of poultry farming in Ukraine, as they cause con-siderable economic damage to poultry farms, regardless of their ownership. As a result of the disease, the poultry lag behind in growth and development, their productivity decreases, feed costs per unit of output in-crease, and in some cases mortality is registered. Helminthiases and eimerioses dominate among poultry endoparasitoses and cause serious diseases, especially in young poultry. Therefore, the aim of the study was to establish the spreading of hen gastrointestinal parasites in Poltava district of Poltava region, Bohodukhiv district of Kharkiv region and Okhtyrka district of Sumy region. The paper presents the results of parasito-logical examination of hens for gastrointestinal parasitoses. Dung samples (at least 25 from each group) were taken from poultry houses where poultry of different age groups were kept. Laboratory studies were carried out in the Scientific Laboratory of the Department of Parasitology of Poltava State Agrarian Univer-sity. Diagnostics was conducted by the modified method of McMaster (McM) with a sensitivity of 50 EHF. To do this, we took 2 g of feces and 28 ml of saturated salt solution, the specific gravity of which was 1.20. The studies have shown a significant spreading of hen parasitic diseases caused by Eimeria spp. (Schneider, 1875) and gastrointestinal nematodes: Ascaridia galli (Schrank, 1788), Heterakis gallinarum (Schrank, 1788), Trichostrongulus tenuis (Mehlis, 1846) and helminths of Capillaria genus (Zeder, 1800). It has been established that poultry association invasions prevail over mono-invasions. It has been registered that the highest EI values in poultry are observed at ascarids (38.6 %) and heterakises (29.6 %) parasitizing, while the lowest – at eimeries (13.6 %) and trichostrongyluses (14.3 %) parasitizing. The obtained data have both scientific and practical value, as they supplement the existing data on the species diversity of pathogens of hen parasitic diseases and the peculiarities of their spreading in different regions of our country.